Kalimat dengan Reduplikasi Verba - Idris, Hatmi (Paradigma: Jurnal Kajian Budaya, 2023)
When complement and object appears all together in one sentence, some verbs can be reduplicated, can not be reduplicated, or can be both reduplicated or not be reduplicated. Reduplicated verb’s example: Ta jiao zhongwen jiao le liang ge xiaoshi ‘He has been teaching Mandarin Chinese for two hours’. Verb can or can not be reduplicated depends on the complement types, the verb meaning and the object charactheristic. This paper will analyze this construction semantically, syntactically, and pragmatically.